Obtenção de nanolignina de resíduos fibrosos do dendê (Elaeis guineesis): avaliação do potencial anti-UV - Nogueira, Izabel de Menezes (2016)
Palm oil (Elaeis guineensis) is the biomass source that has the highest productivity. 5 tons per hectare are produced in a year, when compared to 0.72 tons of soy per hectare in the same period. The diversity of applications and high productivity result in palm oil demand growth. Currently, the oil of the pulp is the most produced and traded vegetable oil in the world, accounting for about 34% of global supply and generating a significant amount of biomass as processing waste. A major constituent of this biomass is lignin which, despite being the second most abundant polymer in nature and the most renewable source of phenolic on earth, is still considered waste and used as fuel in boilers. Thus, in order to increase the potential of biomass, this study characterized the recovered lignin, through the pulping acetosolv method, obtained from the pressing of mesocarp of palm fibers. High power ultrasound was used aiming to obtain nanolignin. The resulting material was applied to films with PVOH matrix. The recovered lignin showed high purity (91.2%), high polydispersity (Mw / Mn = 8.82), main characteristic structure of the monomer p-hydroxyphenyl (81.24%) and glass transition temperature of 32°C. The experimental conditions (20 minutes for ultrasonication and 5 washes) were the most suitable for obtaining nanolignin, yielding 51.8 % of stable nanostructures (zeta potential -54 mV) using high power ultrasound, and confirming the sizes found in MET micrographs. It was also observed that increasing the number of washes resulted in nanolignins with smallers modal diameters and higher zeta potential values, indicating good stability. It was possible to obtain lignin stable nanodispersions. The obtained nanolignins were effectively applied in PVOH matrix films. All films presented anti-UV action.